Pengaruh Kompetisi Politik, Pendapatan Asli Daerah, Dana Alokasi Umum, Dan Opini Audit Terhadap Implementasi E-Government - Sonia Oktaviani; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to determine the effect of political competition, local own-source revenue, general allocation funds, and audit opinions on the implementation of provincial e-Governments in Indonesia in 2011-2018. Data in this study uses secondary data from BPK, BPS, and KPU. The sampling technique uses a purposive sampling method with a total sample of 8 provinces in 5 years. Data analysis uses regression analysis. The results of this study indicate that (1) political competition has a negative and insignificant influence on e-government implementation, (2) Local original income has a positive and significant effect on e-government implementation, (3) general allocation funds have a positive and not significant effect on implementation e-government. (4) audit opinion does not significantly influence the implementation of e-government.